Biofortification and fortification of wheat flour: Qualitative analysis for implementation and acceptance - Yasin, Rahima; Padhani, Zahra A.; Mirani, Mushtaque; Jamali, Muhammad Khan; Memon, Mahwish; Khatoon, Sana; Rai, Riya; Rahman, Areeba; Attaullahjan, Anushka; Das, Jai K. (PLOS, 2025)
This paper comprehensively investigates various aspects of dietary behaviors relating to the usage of wheat flour and sociocultural preferences embedded within rural communities and aims to bridge health gaps resulting from zinc deficiency by introducing zinc bio-fortified and fortified flour in Pakistan. A household and a market study was conducted in Ghotki and Tando Muhammad Khan districts in Sindh, Pakistan. Various stakeholders involved in the wheat-flour industry including farmers, seed suppliers, owners of atta-chakkis and flour mills, grocers and flour merchants, bakers and hoteliers, consumers, and agronomists were interviewed to gauge their knowledge of bio-fortified and fortified wheat-flour. Wheat-flour is a staple food item in Pakistan, however, agricultural output in Pakistan varies across all provinces. Factors that hinder agricultural productivity include a shortfall of essential resources such as irrigation water, superior quality seeds and fertilizers, and machinery. Farmers use primitive methods of farming as they do not have access to modern technologies, information, or training. Wheat flour market vendors and consumers lack awareness of bio-fortified and fortified wheat flour products and believe the only way to create a customer-base is by ensuring that fortified wheat products are available to all and competitively priced compared to traditional options. Additionally, participants misconstrue the process of fermentation and perceive it as unhealthy. The lack of financial resources and awareness restricts adequate promotion of nutrient-rich food products amongst stakeholders involved in the wheat flour industry. Mass awareness campaigns, education and government incentives could bridge the gaps present and encourage wider adoption of bio-fortified and fortified wheat flour. Policy makers and communities can draw on the recommendations made in this paper to introduce and promote zinc bio-fortified and zinc-fortified flour in settings where zinc deficiency is prevalent.